Strategi Kepala Sekolah Dalam Pengembangan Entrepreneurship di SMK Negeri 3 Wonosari Gunungkidul - Mei Nurcahyani Nurcahyani; Pardimin (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to analyze the strengths and weaknesses. analyze opportunities and threats. and analyzing the results of the Entrepreneurship development strategy at SMK Negeri 3 Wonosari Gunungkidul. This research is a qualitative descriptive study. Data were collected using purposive sampling technique by means of interviews, observation and documentation. Data validation is done by member check technique, triangulation technique, and external audit technique. Data analysis data analysis using the Miles and Huberman model with data reduction, data presentation and verification. The results of this study are that the Principal's Strategy in Entrepreneurship Development has the strength in the form of a curriculum that supports Entrepreneurship activities so that there is an increase in product-based learning outcomes and financial management improvements. Meanwhile, the weakness is that there is a maind set that still likes to work and the lack of mastery of foreign languages. The opportunity is increased cooperation with Iduka. Barriers are the lack of marketing skills and the low ability to manage finances. The result of this strategy is an increase in the results of well-managed Entrepreneurship activities based on BLUD management.